A Diversity‐Oriented Approach to Large Libraries of Artificial Macrocycles. Issue 17 (14th April 2021) - Kharchenko, Serhii H.; Iampolska, Anna D.; Radchenko, Dmytro S.; Vashchenko, Bohdan V.; Voitenko, Zoia V.; Grygorenko, Oleksandr O.
Abstract: Diversity‐oriented approach to large artificial macrocycle libraries with a ring size of 13—18 atoms relying on the "build‐couple‐pair" strategy is disclosed. The "couple" phase included three one‐pot steps including consequent amide coupling of N ‐Boc‐monoprotected vicinal diamines with two alkenyl carboxylic acids, followed by ring‐closing metathesis as the key "pair" step. The scope and limitations of the method were established for all three reagents. In particular, various acyclic, mono‐ and bicyclic aliphatic diamine derivatives with the N−C−C−N dihedral angle less than ca . 130° appeared to be suitable substrates. The proposed approach was used to construct a virtual library of 1.8 ⋅ 10 5 macrocycles derived from 12, 283 different scaffolds. More than 40 % of members of this library contained a protected amino function and hence can be suitable for the post‐pairing modification, thus giving rise to at least a billion‐size chemical space based on the REAL‐type synthetic methodology. Validation of the approach under parallel synthesis conditions on a 383‐member subset showed a 61 % success rate over the whole 4–5‐step reaction sequence. Finally, the synthetic approach also worked on a gram scale (up to 8.0 g). Abstract : A diversity‐oriented approach to macrocycle libraries based on the "build/couple/pair" strategy was used to generate a virtual chemical space of 1.8 ⋅ 10 5 compounds, with a possibility to further expansion via the "post‐pairing" modifications. The method relied on a 4–5‐step reaction sequence including ring‐closing metathesis as the key step, with 61 % overall synthetic efficiency under parallel chemistry conditions.